Haploinsufficiency of the basic helix–loop–helix transcription factor HAND2 causes congenital heart defects. Issue 5 (5th March 2020) - Cohen, Ana S. A.; Simotas, Christopher; Webb, Bryn D.; Shi, Huanzhi; Khan, Wahab A.; Edelmann, Lisa; Scott, Stuart A.; Singh, Ram
Abstract: Congenital heart defects (CHDs) are caused by a disruption in heart morphogenesis, which is dependent, in part, on a network of transcription factors (TFs) that regulate myocardial development. Heterozygous sequence variants in the basic helix–loop–helix TF gene heart and neural crest derivatives expressed 2 ( HAND2) have been reported among some patients with CHDs; however, HAND2 has not yet been established as a Mendelian disease gene. We report a 31‐month‐old male with unicommissural unicuspid aortic valve, moderate aortic stenosis, and mild pulmonic stenosis. Chromosome analysis revealed a normal 46, XY karyotype, and a CHD sequencing panel was negative for pathogenic variants in NKX2.5, GATA4, TBX5, and CHD7 . However, chromosomal microarray (CMA) testing identified a heterozygous 546.0‐kb deletion on chromosome 4q34.1 (174364195_174910239[GRCh37/hg19]) that included exons 1 and 2 of SCRG1, HAND2, and HAND2‐AS1 . Familial CMA testing determined that the deletion was paternally inherited, which supported a likely pathogenic classification as the proband's father had previously undergone surgery for Tetralogy of Fallot. The family history was also notable for a paternal uncle who had previously died from complications related to an unknown heart defect. Taken together, this first report of a HAND2 and HAND2‐AS1 deletion in a family with CHDs strongly supports haploinsufficiency of HAND2 as an autosomal dominant cause of CHD.